2016
DOI: 10.1159/000448338
|View full text |Cite
|
Sign up to set email alerts
|

FK506 Binding Protein 10 Is Overexpressed and Promotes Renal Cell Carcinoma

Abstract: Introduction: FK506 binding proteins (FKBPs) function as oncogenes or tumor suppressors by interacting with steroid hormone receptors, kinases, or other cellular factors in addition to intracellular ligands FK506 and rapamycin. In this study, we aimed at evaluating the expression and function of FKBPs in renal cell carcinoma (RCC). Materials and Methods: Thirty-four RCC specimens were analyzed by whole transcriptome sequencing. Small interfere RNA was employed to knockdown FKBP10 in 786-O and A-704 cells, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 29 publications
2
19
0
Order By: Relevance
“…Downregulated FKBP10 can suppress tumor growth in KRAS-driven lung tumors (18). Decreasing the expression of FKBP10 can inhibit the proliferation and migration of renal cancer cells, affecting the cell cycle (21). The transcription factor ETS variant 1 targets FKBP10 to regulate the invasion and migration of prostate cancer cells (19,40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Downregulated FKBP10 can suppress tumor growth in KRAS-driven lung tumors (18). Decreasing the expression of FKBP10 can inhibit the proliferation and migration of renal cancer cells, affecting the cell cycle (21). The transcription factor ETS variant 1 targets FKBP10 to regulate the invasion and migration of prostate cancer cells (19,40).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is increasingly apparent that FKBP members serve a very important role in the formation of tumors and may be considered as novel biomarkers of cancer (14,15). For example, FKBP10 is associated with ovarian cancer (16,17), lung cancer (18), prostate cancer (19), leukemia (20), renal cell carcinoma (21) and colorectal cancer (22).…”
Section: Introductionmentioning
confidence: 99%
“… 26 Decreased expression of FKBP10 inhibits proliferation and migration of renal cancer cells by down-regulating heat shock protein 90 and resulting in cell cycle arrest. 12 In a mouse xenograft model, YK-4-279, which is a small molecule inhibitor of ETV1 , could prevent prostate cancer growth and metastasis. This effect is achieved by targeting FKBP10 .…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11] At present, the role of FKBP10 in tumors is getting more and more attention. Studies have shown that FKBP10 is highly expressed in a variety of tumors, that it promotes tumor progression and is a poor prognostic factor for tumors, such as kidney, 12 lung 13 and prostate cancer. 14 Online data have shown that FKBP10 is a poor prognostic factor for GC, and that it participate in regulating cell adhesion of GC; 15 however, its specific mechanisms in GC are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, several members of the FKBP family, including FKBP9 (also referred to as FKBP60 or FKBP63), FKBP13, FKBP23 and FKBP65, localize to the endoplasmic reticulum (ER) as they contain the ER retention motif H/R/KDEL. Among the ER-residing FKBPs, FKBP65 has been implicated in several types of cancer such as high-grade ovarian serous carcinoma [9], melanoma [10] and renal cell carcinoma [11]. Of interest, FKBP9 is highly amplified in gliomas across most cancer types, as revealed by an initial survey of the TCGA database [12].…”
mentioning
confidence: 99%